1992
DOI: 10.1152/ajpgi.1992.263.3.g345
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and localization of a band 3-related protein from ileum

Abstract: A Cl(-)-HCO3- exchanger in the brush-border membrane mediates active Cl- absorption and regulates intracellular pH in rabbit ileum. The molecular identity of the ileal Cl(-)-HCO3- exchanger has not been established. The best-characterized plasma membrane Cl(-)-HCO3- exchanger is erythroid band 3. Structurally related proteins in nonerythroid tissues comprise an anion exchanger (AE) family. We used the polymerase chain reaction to amplify and clone a cDNA encoding an ileal band 3-related protein (B3RP) from rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 0 publications
1
37
0
1
Order By: Relevance
“…Immunolocalization studies have shown that AE2 is present on apical membranes of villus and crypt enterocytes in ileum (16) and on basolateral membranes of gastric parietal cells (18). The variant that was cloned from ileum is AE2a (16), and previous Northern blot data (10) suggest that in ileum the level of AE2a mRNA is greater than that of AE2b, consistent with the possibility that AE2a is the apical exchanger in ileum. Likewise, AE2b and AE2c mRNAs are abundant in stomach, suggesting that one or both of these variants might mediate Cl Ϫ /HCO 3 Ϫ exchange across the basolateral membrane of the parietal cell.…”
Section: Ae2 CL ϫ /Hcomentioning
confidence: 68%
See 2 more Smart Citations
“…Immunolocalization studies have shown that AE2 is present on apical membranes of villus and crypt enterocytes in ileum (16) and on basolateral membranes of gastric parietal cells (18). The variant that was cloned from ileum is AE2a (16), and previous Northern blot data (10) suggest that in ileum the level of AE2a mRNA is greater than that of AE2b, consistent with the possibility that AE2a is the apical exchanger in ileum. Likewise, AE2b and AE2c mRNAs are abundant in stomach, suggesting that one or both of these variants might mediate Cl Ϫ /HCO 3 Ϫ exchange across the basolateral membrane of the parietal cell.…”
Section: Ae2 CL ϫ /Hcomentioning
confidence: 68%
“…In stomach, AE2 is expressed at high levels on the basolateral membrane of gastric parietal cells (18), where it presumably mediates the exchange of Cl Ϫ and HCO 3 Ϫ that occurs during acid secretion across the apical membrane. In small intestine, it has been localized on the apical membranes of both villus and crypt enterocytes in ileum (16), consistent with a role in both NaCl absorption and HCO 3 Ϫ secretion. The mechanisms underlying the large variations in AE2 mRNA expression levels in different tissues and the mechanisms by which the protein is localized to either apical or basolateral membranes are unknown.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Recently, the molecular cloning of the human AE2 gene has been reported (Medina et al 1997). Expression of the AE2 gene (detected by Northern blotting, immunoblotting, or immunocytochemistry) has been reported in a variety of mammalian organs, such as choroid plexus, stomach, ileum, kidney, testis, cochlea, salivary gland, and liver (Alper et al 1988;Kudrycki et al 1990;Lindsey et al 1990;Chow et al 1992;Parkkila et al 1993;Jons et al 1994;Brosius et al 1995;Negrini et al 1995;Vµzquez et al 1995), in some of which the expressed protein might have a role in hydroionic fluxes into secretions. AE3 and AE3 isoforms appear to be expressed mainly in excitable tissues of the nervous system and in cardiac muscle Kudrycki et al 1990;Linn et al 1992Linn et al , 1995Yannoukakos et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…an I → N substitution in a highly conserved position (783) at the terminal boundary of TM11. Alignment of the 13 known sequences pertaining to different members of the AE1, AE2, AE3 families (Chow et al, 1992;Wood, 1992;Yannoukakos et al, 1994;Kay et al, 1995) revealed that the isoleucine 783 is perfectly conserved through evolution, suggesting that this residue is critical for transmembrane domain structure. Ten other substitutions of conserved residues have been described in association with band 3 deficiency (Alloisio et al, 1993;Jarolim et al, 1994aJarolim et al, , 1995Maillet et al, 1995;Eber et al, 1996).…”
Section: Discussionmentioning
confidence: 99%